Eksplorasi Keseimbangan: Analisis Kritis Buku Teks Bahasa Inggris sebagai Konten Lokal di SDN 04 Maiwa Enrekang - Suhria, Suhria; Irmayanti; Natsir, Indrawati; Rasyid, Asriadi (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2026)
This study aims to analyze whether English textbooks at SDN 04 Maiwa Enrekang as local content accommodate local content and contain contextual or authentic material. The method used is qualitative content analysis with a directed approach to the book "Speed Up English 6" based on the KTSP Curriculum. Results showed that five of the eight chapters contained aspects of local content, although local culture was not explicitly presented. Moreover, this book contains more grammatical material and material that is not completely contextual or authentic. Even though Indonesia has entered the transition period of the Kurikulum Merdeka, SDN 04 Maiwa still uses KTSP-based books for English as local content. The research recommends the development of more contextual and authentic teaching materials, as well as strengthening the position of English as a mandatory competency in order to prepare for the upcoming curriculum.